High velocity innovation : how to get your best ideas to market faster - Radeka, Katherine (Career Press, 2019)
"When a company can get its best ideas to market faster, its leaders gain the confidence that their most important strategic decisions will be executed faithfully, and that their visions for the company's future will be realized. They gain the ability to be agile in response to market changes, pursue new opportunities and achieve ambitious plans for growth. This book will show how companies can accelerate growth with the strategic elements that pull innovation from their best people; a framework for driving innovation that overcomes roadblocks, cultural barriers, and the pressure to sustain the current business; leadership models and metrics for building high accountability and responsiveness into innovation systems; and a road map for accelerating innovation across the business, no matter where it is now"--